A Prospective Randomized Study: The Usefulness and Efficacy of Negative Pressure Wound Therapy with Lipidocolloid Polyester Mesh Compared to Traditional Negative Pressure Wound Therapy for Treatment of Pressure Ulcers - Wooyeol Baek; Nara Lee; Eun Jin Han; Tai Suk Roh; Won Jai Lee (MDPI AG, 2020)
To improve healing of pressure ulcer wounds, it is important to optimize the conditions of the area surrounding the wound. Negative pressure wound therapy (NPWT) promotes wound healing, however, the removal of NPWT can cause pain or focal bleeding, delaying wound healing or causing infection. In this study, we reviewed the efficacy of the lipidocolloid non-adherent dressing (Urgotul®) as a wound contact layer. A total of 38 patients from the same facility who applied NPWT from April 2016 to October 2019 were included and divided into two groups; NPWT with the lipidocolloid non-adherent dressing (group 1, experimental group, 19 patients) and NPWT only (group 2, control group, 19 patients). The condition of the wound was examined prior to NPWT application, at one week, and again at three weeks after application. No significant differences were found between groups for general characteristics, bacterial culture or photo analysis. However, when comparing groups based on the time of examination, there was a significant reduction of the wound size in group 1 (p = 0.001) but not in group 2 (p = 0.082). Therefore, the current study finds that using the lipidocolloid non-adherent dressing as a wound contact layer in NPWT stimulates healing by shrinking the size of the pressure ulcer wound.